ANALISIS DAMPAK SUPERVISI TERHADAP KINERJA PENDIDIK - Aulia Agustina; Bahrani; Akhmad Ramli (Institut Ummul Quro Al-Islami Bogor, 2024)
The teaching performance of teachers in Indonesia has not yet reached a satisfactory level, despite various programs launched by the government. According to a UNESCO survey (Muslim, 2013), the quality of teaching performance of Indonesian teachers ranks 14th out of 14 developing countries, indicating that their performance remains below expectations. Factors such as education level, teaching supervision, training programs, conducive work environments, infrastructure, physical and mental conditions, school leadership, welfare assurance, and managerial skills contribute to this low performance (Fauza, 2010). Among these factors, supervision and motivation play a crucial role in improving teacher performance. Supervision conducted by experts in the field serves to provide guidance and improvement, ensuring that the teaching and learning process can be carried out effectively and with high quality (Engkoswara and Komariah, 2011). This study aims to explore the impact of supervision and motivation on enhancing teaching performance among teachers in Indonesia.